Hybrid Technique for Securing an Object in a Digital Image - Fatin Thair Abd AL Wahab; Omar Muayad Abdullah (Genius Journals, 2023)
The research aims to apply techniques of encryption then applying a steganography for securing the information contended in the image through transferring it on internet. We applied these steps first by encrypting the digital image then hiding this image. We used a hill cipher algorithm for encryption and a Least Significant Bit LSB for steganography. The evaluation of the efficiency of this algorithm is conducted in order to gives the highest encryption rate, and based on the hybrid technique of encryption and information hiding on a group of digital images and based on the mean squared error (MSE) measure, the maximum signal to noise ratio (PSNR), and the structural similarity Index measure (SSIM). The results after applying the Hill Cipher algorithm for encryption with the LSB masking technique gave a good encryption and security rate, as the average of the metrics that were used on a set of digital images were as follows: Average Square Error Rate (Av.mse) gives (5.8184) and (Av.psnr) gives (57.567) and (Av.ssim) gives (0.91573175). These results are considered good and give a high security rate, more confidentiality and difficulty of identification and the presence of confidential information in the cover image.
Keywords: Image Steganography; Hill Cipher; Least Significant Bit LSB